Causes of Indiscipline Among Students as Viewed by Primary School Teachers in Nigeria - Odebode, Aminat Adeola (Universitas Pendidikan Indonesia, 2019)
Indiscipline among students in Nigerian schools remained a source of great concern to stakeholders as it had caused a lot of mental, emotional and physical damage in the society. This research investigated the causes of indiscipline among students as viewed by primary school teachers in Nigeria. The research also examined the influence of gender, school locale, years of teaching experience and educational attainment on the respondents’ views. In addition, this research employed a descriptive survey method. A total of 200 primary school teachers in Nigeria participated in the research. They responded to a researcher-designed questionnaire entitled ‘Causes of Indiscipline Questionnaire’ (CIQ). Then, the psychometric properties of the instrument were established and the collected data were analyzed using both descriptive and inferential statistics. Furthermore, the findings showed that the causes of indiscipline among students as viewed by primary school teachers in Nigeria were societal, governmental, parental, school and students factors respectively. In view of the findings, it is recommended that government and school administrators should formulate policies in schools to curb indiscipline among students.